Reflection on the Past, Present, and Future of Thrombolytic Therapy for Acute Ischemic Stroke. (16th November 2021) - Demel, Stacie L.; Stanton, Robert; Aziz, Yasmin N.; Adeoye, Opeolu; Khatri, Pooja
Abstract : More than 25 years have passed since the US Food and Drug Administration approved IV recombinant tissue plasminogen activator (alteplase) for the treatment of acute ischemic stroke. This landmark decision brought a previously untreatable disease into a new therapeutic landscape, providing inspiration for clinicians and hope to patients. Since that time, the use of alteplase in the clinical setting has become standard of care, continually improving with quality measures such as door-to-needle times and other metrics of specialized stroke unit care. The past decade has seen more widespread use of alteplase in the prehospital setting with mobile stroke units and telestroke and beyond initial time windows via the use of CT perfusion or MRI. Simultaneously, the position of alteplase is being challenged by new lytics and by the concept of its bypass altogether in the era of endovascular therapy. We provide an overview of alteplase, including its earliest trials and how they have shaped the current therapeutic landscape of ischemic stroke treatment, and touch on new frontiers for thrombolytic therapy. We highlight the critical role of thrombolytic therapy in the past, present, and future of ischemic stroke care.